2021
DOI: 10.2147/cmar.s311326
|View full text |Cite
|
Sign up to set email alerts
|

Adenosquamous Carcinoma of the Uterine Cervix – Impact of Histology on Clinical Management

Abstract: Introduction Historically, the incidence rate of cervical cancer (CC) in Eastern Europe and particularly in Bulgaria has constantly been higher than that in the other European countries. Adenosquamous carcinoma (ASC) is a rare histological subtype of CC with incidence rate of less than 6 per 100,000. We aimed to analyze the epidemiology and prognosis of all Bulgarian patients with ASC, registered at the Bulgarian National Cancer Registry (BNCR), and to compare patients’ characteristics and outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Nevertheless, according to Stolnicu et al, in practice, diagnoses of this subtype are frequently made erroneously in tumors lacking unequivocal squamous and/or glandular differentiation [ 39 ]. A recent analysis of the morphology of this subtype revealed that, in 42% of cases initially diagnosed as adenosquamous carcinoma, a reclassification was necessary [ 9 ]. Thus, the observed pattern in our results, instead of providing insights for the characterization of cervical adenosquamous carcinoma, may suggest the need to reconsider the diagnosis of these six mixed samples, which appear to resemble dedifferentiated cervical tumors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, according to Stolnicu et al, in practice, diagnoses of this subtype are frequently made erroneously in tumors lacking unequivocal squamous and/or glandular differentiation [ 39 ]. A recent analysis of the morphology of this subtype revealed that, in 42% of cases initially diagnosed as adenosquamous carcinoma, a reclassification was necessary [ 9 ]. Thus, the observed pattern in our results, instead of providing insights for the characterization of cervical adenosquamous carcinoma, may suggest the need to reconsider the diagnosis of these six mixed samples, which appear to resemble dedifferentiated cervical tumors.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to cervical squamous cell carcinoma, cervical adenocarcinoma exhibits greater aggressiveness, a higher rate of metastasis, inferior prognosis, and reduced rates of survival [ 8 ]. Cervical adenosquamous carcinoma is an infrequent subtype (with an incidence rate of less than 6/100,000 [ 9 ]) that is characterized by the presence of both squamous cell and glandular differentiation [ 10 ]. Few reports, often inconsistent, have documented the survival outcomes and prognostic factors in patients with this histological subtype [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of adenosquamous carcinoma ranges from 3% to 10% [ 20 ], although some series may overestimate this diagnosis, as adenocarcinomas, alongside squamous metaplasia and mucus-secreting adenocarcinomas, can mimic adenosquamous carcinoma. In the present study, the frequency of adenosquamous carcinoma was 3.1%, similar to the rate described by Yordanov et al [ 20 ] in Bulgaria, of 3.2%. Adenosquamous carcinoma increased the risk of CM development by 7.3-fold (95% CI=2.87–18.73).…”
Section: Discussionmentioning
confidence: 99%
“…Association with Human Papilloma Virus types 16 and 18 is seen frequently [4][5][6][7][8][9][10][11]. A monoclonal origin of ASCC has been confirmed and is thought to arise from subcolumnar reserve cells in the basal layer of endocervix [12].…”
Section: Its Precursors Are High-grade Squamous Intraepithelial Lesio...mentioning
confidence: 99%
“…The diagnosis of ASCC requires the identification of unequivocal malignant glandular and squamous differentiation in the tumor [6,7]. This rare subtype of cervical carcinoma is an aggressive tumor and has a worse prognosis as compared to squamous cell carcinoma [8].…”
Section: Introductionmentioning
confidence: 99%